Management of Elementary School and Community Relationship - Lestariningsih, Dwi Kristina; Ayu, Reka Tri; Lodan, Lusia; Fajriana, Syahwa Gadis; Pertiwi, Santhi (LPPM Universitas Mohammad Husni Thamrin, 2025)
Elementary schools as the first line in the implementation of formal education have an important role in building a strong foundation for student development. The interaction that is well established between elementary schools and the community is not just a temporary relationship, but rather a strategic and sustainable management process. The importance of MRSM is increasingly evident in facing the demands of education that are increasingly complex and changing. This study examines how important it is to manage the relationship between elementary schools and the community in supporting educational success. The purpose of this study is to find effective strategies in building sustainable collaboration between schools and various elements of society. The method used is a Systematic Literature Review (TLS), which includes an analysis of literature from the last five to ten years that is relevant to the theme of the relationship between schools and the community. The findings of this study indicate that community participation in educational activities, the use of information media, and open and participatory communication are key factors in creating productive partnerships. School committees, community leaders, and the private sector have important roles in improving the quality of learning and student character. Regular assessment of partnership programs is also important to ensure the effectiveness and sustainability of the relationship. Recommendations from this study include the need for a systematic managerial approach, increased communication capacity in schools, and the use of information technology to support broader and more active community involvement.